Enumeration of interleukin 2-producing cells from rat spleen - Makonkawkeyoon S. (2014)
A method for the enumeration of IL2-producing cells from rat spleen has been developed. Rat spleen cells were stimulated with concanavalin A (Con A), washed, then mixed with IL2-dependent cells (3 day Con A blasts) and plated in soft agar. Clusters of IL2-dependent cells formed around IL2-producing cells, giving colonies which were easy to count under a dissecting microscope. All experimental factors influencing development of colonies of IL2-producing cells surrounded by IL2-dependent cells were evaluated and set up. Optimum number of effector cells was 2.5 x 10(5) cells/culture, while optimum number of IL2-dependent cells was 6 x 10(6) cells/culture. Optimum concentration of Con A for IL2 stimulation was 40 micrograms/ml with an optimal stimulation time of 10 hours. Optimum incubation time for development of IL2-producing cell colonies was 5 days. The number of IL2-producing cells by this technique had a good correlation with the level of IL2 in the cell culture fluid (r = 0.885). When colonies were aspirated from agar and stained by Wright stain, a big purple stained cell at the center was surrounded by small cells in almost all colonies examined. All cells from colonies were fluoresed with anti-mouse Thy 1.2-fluorescein conjugate. However, they were negative with anti-mouse Ig-fluorescein conjugate. The number of IL2-producing cells was 816-2080 cells/10(6) of rat spleen cells with mean +/- S.E.M. = 1404 +/- 154/10(6) cells.